18 Balance training alone is as effective as balance training augmented with sensory treatments in those with chronic ankle instability. (12th October 2015) - Burcal, CJ; Trier, AY; Wikstrom, EA
Abstract : Background: Research demonstrates that both motor (balance training) and sensory (massage, joint mobilizations) interventions are effective at improving chronic ankle instability (CAI) associated impairments but limited information is available about the effectiveness of combined interventions. Objective: To determine if using sensory targeted ankle rehabilitation strategies (STARS) concurrently with balance training results in greater improvements in static postural control than balance training alone in those with CAI. Design: Randomised controlled trial. Setting: Research Laboratory. Patients (or participants): Twenty-four participants with self-reported CAI were randomly assigned to two groups: balance training (BT; age = 21.2 ± 1.6 years; height = 170.8 ± 15.1 cm; body mass = 73.0 ± 24.8 kg; FAAM = 85.9 ± 8.8%; FAAM-S = 68.2 ± 13.4%) and balance training with STARS (BTS; age = 21.4 ± 2.4 years; height = 168.8 ± 10.9 cm; body mass = 71.9 ± 20.3 kg; FAAM = 84.8 ± 7.3%; FAAM-S = 69.0 ± 12.9%). Interventions (or assessment of risk factors): Subjects completed a 4-week (12 sessions) balance training protocol on their involved limb consisting of hopping, reaching tasks, and static balance tasks with eyes open and closed. Progression was based on error free performance. The BTS group received a 5-minute STARS treatment prior to each training session consisting of calf stretching, talocrural joint traction, Grade III A-P joint mobilizations, and plantar massage. Main outcome measurements: Time-to-boundary (TTB) minima, means and standard deviations were calculated for anterior-posterior (AP) and medial-lateral (ML) directions during eyes open and eyes closed single-limb balance at baseline and 24 h after protocol completion. Results: Group differences were evaluated using separate 2-way repeated measures ANOVAs. No significant group or time main effects for eyes open TTB (p > 0.05) was identified. However, a time main effect for eyes closed TTB was observed for AP mean (p = 0.031) and AP standard deviation (p = 0.019). Conclusions: A brief (5-minute) STARS treatment given concurrently with a balance training protocol does not improve static postural control in those with CAI any better than an error based dynamic balance training protocol does alone. Future research should explore the manipulation of different parameters associated with combined interventions.